2022
DOI: 10.1002/jip.1586
|View full text |Cite
|
Sign up to set email alerts
|

The effects of building and maintaining rapport on cooperative mock eyewitness recall

Abstract: Although building rapport before an investigative interview is recommended-and sometimes empirically beneficial-to eyewitness memory, no research has experimentally examined the effects of maintaining rapport during a witness interview on adult eyewitness recall. As a result, the present study assessed the impact of rapport on eyewitness recall accuracy by comparing a pre-interview rapport only condition with a maintained rapport condition (where rapport was built before and maintained during the interview) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…For instance, our study did not yield a main effect of rapport on crime details, which is unlike prior research finding that building rapport is directly linked—causally or otherwise—to the amount of information provided by suspects, confession diagnosticity, or the comprehensiveness of their accounts (Alison et al, 2013, 2014; Collins & Carthy, 2019; Hwang & Matsumoto, 2020; Kelly et al, 2016; Meissner et al, 2014; Wachi et al, 2018; Walsh & Bull, 2012). However, other experimental research has not supported a main effect for rapport (e.g., Villalba, 2014; Wolfs et al, in press), or has found that rapport only indirectly affects information gain through increased positivity and cooperation (Brimbal et al, 2019; Christiansen et al, 2018). Additionally, results of the present study failed to support a moral minimization main effect, which seems to differ from the results found in previous research that had used some form of minimization (Klaver et al, 2008; Russano et al, 2005).…”
Section: Discussionmentioning
confidence: 94%
“…For instance, our study did not yield a main effect of rapport on crime details, which is unlike prior research finding that building rapport is directly linked—causally or otherwise—to the amount of information provided by suspects, confession diagnosticity, or the comprehensiveness of their accounts (Alison et al, 2013, 2014; Collins & Carthy, 2019; Hwang & Matsumoto, 2020; Kelly et al, 2016; Meissner et al, 2014; Wachi et al, 2018; Walsh & Bull, 2012). However, other experimental research has not supported a main effect for rapport (e.g., Villalba, 2014; Wolfs et al, in press), or has found that rapport only indirectly affects information gain through increased positivity and cooperation (Brimbal et al, 2019; Christiansen et al, 2018). Additionally, results of the present study failed to support a moral minimization main effect, which seems to differ from the results found in previous research that had used some form of minimization (Klaver et al, 2008; Russano et al, 2005).…”
Section: Discussionmentioning
confidence: 94%
“…We are not alone in reporting null effects of rapport on witness recall. Wolfs et al (2022) and Kieckhaefer et al (2014) did not replicate rapport building's beneficial impact on eyewitnesses' reports. Moreover, it is possible that unpublished studies have similarly failed to detect a relationship between rapport and witness recall—the difficulties of publishing null effects may be obscuring rapport's real impact on eyewitness memory.…”
Section: Discussionmentioning
confidence: 96%
“…Those exposed to verbal and visual evidence with rapport were most likely to corroborate the falsehood, but rapport building alone also predicted corroboration of the false accusation. Wolfs et al (2022) investigated whether the maintenance of rapport during the substantive interview affected eyewitness recall compared to pre‐interview rapport building only, or no rapport at all. They reported null effects of rapport on witness recall quantity and quality.…”
Section: Introductionmentioning
confidence: 99%
“…Some experimental studies support the usefulness of rapport for increasing the likelihood as well as the accuracy of disclosure from both child (Almerigogna et al., 2008; Leander et al., 2009) and adult witnesses (Collins et al., 2002; Kieckhaefer et al., 2014; Nash et al., 2014). Others, however, failed to find beneficial effects of rapport in mock witness scenarios (e.g., Sauerland et al., 2018; Wolfs et al., 2022; see Gabbert et al., 2021 for a recent review). Thus far, little is known about to what extent and under which circumstances rapport affects disclosure.…”
Section: Rapport‐building: Chat Versus In‐person Witness Interviewsmentioning
confidence: 99%